Smoking during Pregnancy Is a Risk Factor for Executive Function Deficits in Preschool-aged Children - Daseking, M.; Petermann, F.; Tischler, T.; Waldmann, H.-C. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Maternal nicotine use during pregnancy has a negative impact on the child. Numerous studies have demonstrated an association between smoking during pregnancy and psychological deficits. This study looks at deficits in executive functioning in preschool-aged children. Methods: The executive functioning of preschool children was assessed by asking parents to complete the parental form of the Behavior Rating Inventory of Executive Functions – Preschool Version (BRIEF-P, German version). The results for preschool children whose mothers had smoked during pregnancy (n = 71) were compared with those of a control group. In a subsample, parental assessments of children of smokers (n = 42) and non-smokers (n = 27) were complemented by the teacher form of the BRIEF-P (German version), which allowed inter-rater agreement (parents vs. preschool teachers) to be assessed. Results: An increased incidence of executive function deficits was noted in the children of smokers, based on parental assessment. Clinically relevant deficits were particularly evident with regard to inhibition, with inhibitory deficits in children of smokers found to be almost four times higher than in the control group (p = 0.006). Inhibitory deficits were reported both by parents and by preschool teachers. Discussion: The increased percentage of executive function deficits described here, particularly the increased inhibitory deficits, confirms the current state of research on smoking during pregnancy. Poor inhibition or impulse control is a key symptom of ADHD.
Keywords: nicotine; pregnancy; executive functions; ADHD; BRIEF-P